Effect of two organic fertilizers on food webs of soil cultivated with blackberry - Orozco Aceves, Martha (2017)
Soil fertilization with organic fertilizers comprises a practice that improves the soil biological properties; however, the effect of these on the soil food web (SFW) has been scarcely studied. The aim of this study was to determine the effect of two commercial organic fertilizers on the structure of the SFW associated with roots of blackberry plants (Rubus adenotrichos). The research was conducted in two blackberry plantations located one in San Martín de León Cortés, and the other one in Buena Vista de Pérez Zeledón in San José, Costa Rica, from August to December, 2010. In the two plantations, plants were fertilized with compost or vermicompost. The roots of blackberry plants surrounding soil were sampled in order to quantify groups of the SFW through the following techniques: bacteria and filamentous fungi by plate count, protozoa by the most probable number, spores from arbuscular mycorrhizal fungi and nematodes by flotation-centrifugation, microarthropods, macroarthropods, and worms were directly counted in soil samples. The dataset was analyzed by multidimensional scaling analysis. The addition of organic fertilizers to soil caused a differential effect on the structure of the SFW (as compared with non-fertilized soils). The effect differed in soil from each of the experimental plantations according to fertilizer type. The groups of organisms mainly affected were actinomycetes and protozoa, which implies that the structure of SFW and consequently, the function of soil were not affected by the addition of organic fertilizers.